Microbe and plant-assisted remediation of organic xenobiotics, in Handbook on Assisted and Amendment-Enhanced Sustainable Remediation Technology - Pinto, Ana Paula (2022)
Environmental pollution with organic xenobiotics viz. polycyclic aromatic hydrocarbons (PAHs) is a worldwide problem, and the development of emerging and sustainable remediation technologies for the decontamination of impacted sites are extremely meaningful. In soils, PAHs can be subject to different processes, and can be degraded by several physical, chemical and biological processes. These compounds are generally difficult to (bio)degrade in natural matrices and their persistence in natural ecosystems can increase with the number of rings as well as with their molecular weight. Different physical, chemical, thermal, biological and integrated approaches are attainable to remediate the pollution caused by organic xenobiotics (OXs) including PAHs. The high costs and limited efficiency of conventional treatments have impelled the continued effort to develop more efficient, sustainable, environmentally friendly and cost-effective remediation technologies applying advanced biotechnological tools and rhizosphere engineering, with special emphasis on those based on biological remediation abilities of plants and microorganisms and their synergistic approaches. Recent studies bet on a growing effort to increase the effectiveness of phytoremediation in polluted environments, increasingly exploring the synergies present in plant-microbe interactions. The combined use of plants and endophytic bacteria (EB) is an emerging and promising approach for remediation of soils contaminated with OXs and has gained increasing acceptance as a viable and innovative clean-up technology. This chapter reviews/analyzes the important impacts resulting from the presence of PAHs in the environment and its relationship with their physicochemical characteristics, trying to describe the different and more suitable ecologically correct phytotechnologies, particularly exploring the association between plants and microorganisms, with special focus on endophytes.